Oral controlled-release morphine and gut function: a study in volunteers - Clyburn, P A; Rosen, M (European journal of anaesthesiology, 1989)
The effects of a single 30-mg tablet of oral controlled-release (OCR) morphine (MST) on gastric emptying and small-intestine transit time (SITT) were compared with placebo in a double-blind, cross-over trial, on ten healthy volunteers. Gastric emptying was measured by paracetamol absorption and SITT by the rise in breath hydrogen after a carbohydrate test meal. There was no alteration in the absorption of paracetamol given 90 min after OCR administration but this was well before peak plasma morphine levels occurred. However, 30% of subjects had nausea after OCR morphine. Mean SITT in controls was 300 min (range 120-460 min) which was significantly prolonged in eight of the 10 subjects (P less than 0.05) and beyond the study period of 480 min in six subjects. Further study is required to determine how this compares with intramuscular morphine. Peak blood levels of morphine occurred at 3 h with a mean plasma concentration of 12.3 micrograms l-1 (SEM 2.0 micrograms l-1).